A Rare Case of Solitary Fibrous Tumor of the Breast in a Healthy 40-Year-Old Woman - Marissa Yaldo; Arif Musa; Michael Aulicino; Brigitte Berryhill (Case Reports in Radiology)
Solitary fibrous tumor (SFT) is a rare neoplasm of mesenchymal origin that is primarily found in the lungs but can be found in other locations such as the retroperitoneum, deep soft tissues of the proximal extremities, abdominal cavity, head, and neck. Moreover, SFTs found in the breast are extremely rare and, oftentimes, are found incidentally during screening mammography. Our case presents an exceptionally rare occurrence of a SFT in the breast of a 40-year-old woman. This rarity is underscored by its classification as a SFT and its unusual location within the breast tissue as well as this patient’s young age. This case emphasizes the importance of a thorough evaluation with both imaging and histopathology for diagnosing SFTs. It also addresses the potential difficulties that may arise during this process, especially for radiologists who may have limited experience encountering SFTs.